SWEET - Towards a Digital Wellbeing and Occupational Health Platform in the Age of the COVID-19 Pandemic - Paredes, Pablo E.; Goel, Rahul; Mauriello, Matthew L. (2020)
ABSTRACT The COVID-19 pandemic continues to affect work life and the mental health burden globally. Asking millions of workers to work from home or go back to work with the risk of being infected is a problematic aspect of the pandemic increasing stress and negatively impacting productivity. The objective of occupational and precision health research and practice is to precisely measure and sustain workers’ mental health and productivity. Best practices for the workplace propose the need to identify the early effects of factors such as psychological distress and develop interventions for the proactive treatment of pre-disease stages of mental disorders. In this position paper, we propose the development of a novel platform for workers that integrates continuous sensing and long-term self-regulation interventions. The Stanford Wellbeing and Emotional Education Technology Platform (SWEET) is a digital wellbeing and occupational health platform designed as a compendium of ubiquitous technology modules to help manage stress and productivity, during and post-pandemic, while amplifying research on occupational precision mental health. Here, we discuss adapting our system in the wake of COVID-19. Keywords stress management, productivity, precision health, occupational health, mental health, digital wellbeing, prediction, sensing, interventions, pandemic, COVID-19 ABOUT THE AUTHOR/S Pablo E. Paredes Stanford University pparedes@stanford.edu Pablo E. Paredes earned his Ph.D. in Computer Science from the University of California, Berkeley in 2015, with an emphasis on Human-Computer Interaction (HCI), advised by Prof. John Canny. He is a Clinical Assistant Professor in the Psychiatry & Behavioral Sciences Department in Stanford University School of Medicine and leads the Pervasive Wellbeing Technology Lab. Stanford Profile: https://profiles.stanford.edu/pablo-paredes-castro Rahul Goel Stanford University rahulg20@stanford.edu Matthew Louis Stanford University mattm401@stanford.edu If you wish to discuss the research, please contact the Pervasive Wellbeing Technology Lab at Stanford University by emailing: pparedes@stanford.edu New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).